2016
DOI: 10.3906/sag-1504-139
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of pressure ulcer in patients on mechanical ventilation andeffects of selected risk factors on pressure ulcer development*

Abstract: IntroductionA pressure ulcer (PU) is localized tissue damage in the dermis and subdermis caused by compression, friction, shearing, and other factors (1). It is commonly encountered in all hospitalized patients, especially those in intensive care units (ICUs) (2). The incidence of PU was found to increase from 4% to 49% in Denmark and vary from 38% to 24% in Germany (3) and from 14% to 42% in the United States (4,5). Studies from Turkey showed that the incidence of PU varied between 15% and 29% (6-8).Mobilizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 22 publications
1
16
0
1
Order By: Relevance
“…[4,8] In the previous studies, it was shown that pressure ulcers developed significantly at second week of mechanical ventilation treatment and mechanical ventilation treatment lasting longer than 20 days might be associated with pressure ulcers. [3,9] At the end of this current study, the incidence of stage I pressure ulcer was found to be 10.8% at 10 hours after the initiation of mechanical ventilation treatment and the incidences were found to be 58.5% at first week and 71.15% at second week as parallel to the data in the literature. This situation confirmed that pressure ulcer development rates increased with the extension of the duration of mechanical ventilation treatment.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…[4,8] In the previous studies, it was shown that pressure ulcers developed significantly at second week of mechanical ventilation treatment and mechanical ventilation treatment lasting longer than 20 days might be associated with pressure ulcers. [3,9] At the end of this current study, the incidence of stage I pressure ulcer was found to be 10.8% at 10 hours after the initiation of mechanical ventilation treatment and the incidences were found to be 58.5% at first week and 71.15% at second week as parallel to the data in the literature. This situation confirmed that pressure ulcer development rates increased with the extension of the duration of mechanical ventilation treatment.…”
Section: Discussionsupporting
confidence: 83%
“…Mechanical ventilation treatment has been reported to be a factor causing pressure ulcers due to its impairing effect on blood circulation at epidermal and subcutaneous tissue and on the balance between ventilation-perfusion by affecting pumping function of the heart. [9,11] In a study which was conducted in six centers, it was indicated that patients who were on mechanical ventilation treatment were at a higher risk compared to the others receiving inpatient treatment. [3] In a study which was carried out in surgical intensive care units, development of pressure ulcers was significantly enhanced by the increase in the days of ventilation, dialysis and gaita incontinence; and besides, the number of days for using norepinephrine and lactic acid level in arterial blood were determined to create a high risk for pressure ulcers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Günümüzde (17). Ağrı, hipotansiyon, hipertermi, azalmış bilinç seviyesi, hipoalbüminemi, düşük hemoglobin seviyeleri, malnütrisyon, obezite, dehidrasyon, sigara içmek, ileri yaş, diyabet, aşırı nem, hastanede kalış süresinin uzaması, uzamış mekanik ventilasyon süresi bilinen diğer risk faktörleridir (13,18). Çalışmamızda sakrum ve koksiks en sık bası yarası gelişen bölgelerdi (pelvik alan %88, torakonter %12) ve mekanik ventilasyon gün ortalaması çok uzundu (50,21/gün).…”
Section: Discussionunclassified